Custom-made standardised over-dressings for torso burns; economical and efficient - Mobinulla Syed; Azzam Farroha; Bruce Azzam (Indian Journal of Plastic Surgery, 2012)
Introduction: Torso burns following debridement and skin grafting usually require fairly complex dressings. The dressing consists of an interface layer, an absorbent layer and a retaining layer. Although numerous inner dressings are now available from multiple manufacturers, Gamgee dressing (pad of cotton and gauze) is often used as an outer absorbent dressing. Dressing the torso is usually a challenge, and the purpose of this paper is to present a custom-made over-dressing for torso burns, which reflects the current practice at our centre. Materials and Methods: A U-shape cut is made at one end of the Gamgee to design the shoulder straps. This custom-made dressing is held in place by a custom-designed netted vest. Results: This custom-made over-dressing for the torso was found to be comfortable for patients, easily made from locally available materials, easy to apply, absorbent and not restrictive of movement. The shoulder straps prevent sliding of the Gamgee, and in a nonrestrictive way. The netted vest provides the required compression to keep the Gamgee in firm contact with the inner layers of the dressing without compromising respiration. Conclusion: In this report, we present our practice of a custom-made dressing that is very efficient and economical. We hope that this information will be of practical use to other centres managing burns.